2021
DOI: 10.3390/molecules26154649
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Water-Dispersed Biodegradable Polyurethane-Silk Composite Sponge Using 13C Solid-State Nuclear Magnetic Resonance as Coating Material for Silk Vascular Grafts with Small Diameters

Abstract: Recently, Bombyx mori silk fibroin (SF) has been shown to be a suitable material for vascular prostheses for small arteries. In this study, we developed a softer SF graft by coating water-dispersed biodegradable polyurethane (PU) based on polycaprolactone and an SF composite sponge on the knitted SF vascular graft. Three kinds of 13C solid-state nuclear magnetic resonance (NMR), namely carbon-13 (13C) cross-polarization/magic angle spinning (MAS), 13C dipolar decoupled MAS, and 13C refocused insensitive nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…The same group performed an implantation experiment centered around SF artificial vascular grafts coated with SF-PU composite sponges in rats, demonstrating a high patency rate and confirming the proper growth of vascular endothelial cells inside the SF-PU graft at 4 weeks from implantation. These results showed that these biodegradable SF-PU composites could be a strong candidate for applications as small-diameter artificial vascular grafts [132].…”
Section: Silk Fibroin Compositesmentioning
confidence: 75%
“…The same group performed an implantation experiment centered around SF artificial vascular grafts coated with SF-PU composite sponges in rats, demonstrating a high patency rate and confirming the proper growth of vascular endothelial cells inside the SF-PU graft at 4 weeks from implantation. These results showed that these biodegradable SF-PU composites could be a strong candidate for applications as small-diameter artificial vascular grafts [132].…”
Section: Silk Fibroin Compositesmentioning
confidence: 75%